2015
DOI: 10.1016/j.brainres.2015.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel polyglutamine-expanded aggregation species in spinal and bulbar muscular atrophy

Abstract: Polyglutamine-repeat disorders are part of a larger family of neurodegenerative diseases characterized by protein misfolding and aggregation. In spinal and bulbar muscular atrophy (SBMA), polyglutamine expansion within the androgen receptor (AR) causes progressive debilitating muscular atrophy and lower motor neuron loss in males. Although soluble polyglutamine-expanded aggregation species are considered toxic intermediates in the aggregation process, relatively little is known about the spectrum of structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The nature of the oligomeric aggregates associated with the second scheme can be quite heterogeneous and dependent on the specific polyQ-containing protein. 30, 62, 63 It should be noted that oligomers that are off pathway to fibril formation may also form.…”
Section: Polyq-mediated Protein Aggregation Is a Complex Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the oligomeric aggregates associated with the second scheme can be quite heterogeneous and dependent on the specific polyQ-containing protein. 30, 62, 63 It should be noted that oligomers that are off pathway to fibril formation may also form.…”
Section: Polyq-mediated Protein Aggregation Is a Complex Processmentioning
confidence: 99%
“…78 A novel oligomeric specie of the androgen receptor with expanded polyQ was isolated from PC12 cells via cryo-extraction, and these oligomers were less compacted compared with late stage aggregates and correlated with toxicity. 62 …”
Section: Oligomers Formed By Expanded Polyq-containing Proteins Are Dmentioning
confidence: 99%
“…By Western blotting and filter retardation assay we found accumulation of high-molecular weight (HMW) species and micro-aggregates in the brainstem and skeletal muscle of 8-week-old AR100Q mice (Figure 1A and Supplementary Figure 2A-D). AR aggregation and inclusion body formation have been extensively characterized in neurons, but not in muscle (12,(16)(17)(18)(19). In skeletal muscle polyQ-expanded AR aggregation was 2% sodium dodecyl sulphate (SDS)-resistant and was detected as early as 4 weeks of age mainly in muscles composed of both fast-glycolytic and slow-oxidative fibers and that degenerate in SBMA, such as quadriceps, gastrocnemius, and tibialis anterior (TA), as well as muscles composed of fast-glycolytic fibers, such as extensor digitorum longus (EDL), and to a lower extent in muscles composed of slowoxidative fibers, such as soleus, and diaphragm and heart, which are only mildly affected in SBMA, indicating that polyQ-expanded AR aggregation occurs early and is affected by muscle metabolism.…”
Section: Ar100q Mice Display Age-dependent Ar Aggregation Inclusion mentioning
confidence: 99%
“…Rather, SBMA results from partial AR LOF in combination with polyQ-AR neomorphic gain of function (GOF) (15). A key factor contributing to the toxic GOF of polyQ-AR is the deposition of the disease protein into micro-aggregates and inclusion bodies, and specific types of polyQ-AR-positive aggregates have been linked to neurotoxicity in vitro and in vivo (12,(16)(17)(18)(19). Although the androgen-dependent nature of disease and experimental evidence support chemical and physical castration as a therapeutic strategy for SBMA (10,11,13), clinical trials based on this approach showed benefits limited to a subset of patients (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…21 The latter two pools (40–500 and >500 S) are predicted to have variable SDS sensitivity as judged by the migration of these intermediate pools in the SDD-AGE experiments and may be a reflection of the degree of compaction. 64 …”
Section: Discussionmentioning
confidence: 99%